A measurement of the Higgs boson mass in the diphoton decay channel - Sirunyan, A. M. (2020)
A measurement of the mass of the Higgs boson in the diphoton decay channel is presented. This analysis is based on 35.9 fb−1 of proton-proton collision data collected during the 2016 LHC running period, with the CMS detector at a centre-of-mass energy of 13 TeV. A refined detector calibration and new analysis techniques have been used to improve the precision of this measurement. The Higgs boson mass is measured to be mH = 125.78±0.26 GeV. This is combined with a measurement of mH already performed in the H → ZZ → 4 decay channel using the same data set, giving mH = 125.46 ± 0.16 GeV. This result, when further combined with an earlier measurement of mH using data collected in 2011 and 2012 with the CMS detector, gives a value for the Higgs boson mass of mH = 125.38 ± 0.14 GeV. This is currently the most precise measurement of the mass of the Higgs boson.